The impact of board composition, ownership and CEO duality on audit quality: the Malaysian evidence / Wan Zanani Wan Abdullah, Shahnaz Ismail and Nurasyikin Jamaluddin - Wan Abdullah, Wan Zanani; Ismail, Ismail; Jamaluddin, Nurasyikin (Accounting Research Institute (ARI) & Faculty of Accountancy, 2008)
Corporate governance is an important element in monitoring the process of financial reporting system. There are three monitoring mechanisms that are theoretically used to ensure the credibility of corporate governance, namely, external auditor, an internal auditing and the directorships. The trends of corporate governance model in developed countries cannot explain the reality of monitoring process of financial reporting in developing countries especially in Asian countries like Malaysia. Therefore, it is important to know to what extent the corporate governance of the Malaysian listed companies has been effective in meeting the responsibility of monitoring the process of financial reporting system? Generally, this study intended to examine an effective component of corporate governance in a Malaysian listed companies and relationship with the audit quality. A total of 655 companies were selected as the sample representing 73.84% of total number of companies across industries in year 2003. The analysis of logistic regression was used to investigate the relationship between dependent and independent variables. Results show that two independent variables had a significant relationship with audit firm size. They were board independence and nonfinancial institutional ownership. The executive directors’ ownership and CEO/chairman had a negative relationship but not significant with audit quality. Whereas non-executive directors’ ownership and financial institutional ownership showed a positive relationship with audit quality however, it was not significant. The findings posit that both board independence and institutional ownership are important factors to the companies listed at Bursa Malaysia perform effectively. These two elements will improve the decision making process to be more transparent and objective and enhance the independence in selecting quality of external auditor. This study suggests that companies tend to audit by Big 4 if the level of board independence and institutional ownership increase. So, these criteria should be taken seriously by companies’ top management as well as regulator in order to increase the audit quality and then the quality of financial reporting.